Entrepreneurship: Entrepreneurial Decision Making Factors During the Covid-19 Pandemic - Andi Ismail Marasabessy (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This research was conducted with the aim of knowing the factors that cause a person to make entrepreneurial decisions during the Covid-19 pandemic. The research method in this study uses a descriptive qualitative approach. The object of research in this study is the SME entrepreneurs in Batu Merah village. The results showed that covid-19 provided opportunities for people around Batu Merah village to carry out entrepreneurial activities. Although overall Covid-19 affects all sectors of life for the people of Ambon City. Another result found was that the presence of Indomaret and Alfamidi was a factor in the emergence of new MSMEs around the Batu Merah village of Ambon City. Many people take advantage of the presence of Indomaret and Alfamidi to start a business by utilizing the space in front of Indomaret and Alfamidi.